The protection of international private investment : Nigeria and the world community - Mummery, David R. (New York : F. A. Praeger, 1968)
''In the realm of public policy, '' it has been said, there are no economic problems, no political problems, no legal problems; there merely problems.'' This book examines some of the problems involved in the protection of foreign private investment in the developing countries.
Includes bibliographical references and index
uaa 25/01/219
Loans.
Keywords: Investments, Foreign; Investments, Foreign--Law and legislation; Investments, Foreign; Nigeria